Digitized Identification of Indigo Natural Dyeing on Batik and Non-Batik Fabrics - Firmansyah, Almira (Indonesian Journal of Visual Culture, Design, and Cinema, 2024)
Natural coloring in textiles has regained favor as the sustainable fashion movement grows. Fabric colour digitisation can help with data inventory of natural dyed textiles because digital data could endure longer than physical sample artifacts. In this research, digitization was performed on standardized fabric samples: cotton fabric dyed with indigo natural dyestuff and processed with batik and non-batik treatment. Indigo dye is made from the indigo plant (Indigofera tinctoria) and is fixed with quicklime (Calcium Oxide), which serves as both the initial and final mordant. Fabric dyeing was repeated three, six and nine times until the desired hue is reached. The final fabric samples were then scanned to produce discrete color values in RGB format. Color digitization of batik and non-batik fabrics produces content which can be used in digital mediums.